Global blind spots in soil health research overlap with environmental vulnerability hotspots - Maurício Roberto Cherubin; Carlos Roberto Pinheiro Junior; Lucas Freitas Nogueira Souza; Lucas Pecci Canisares; Tiago Osório Ferreira; Carlos Eduardo Pellegrino Cerri; Budiman Minasny; Pete Smith (Communications Earth & Environment)
Abstract Healthy soils are essential for sustaining ecosystem services and human well-being. However, poorly distributed global soil health research hinders the development of local solutions to promote soil security. Here, we analyzed 31,999 articles published worldwide on soil health and its relationship to major threats to soil and global crises. Our findings reveal a significant increase in soil health publications; however, this scientific production is concentrated in European countries, China, the United States, India, and Brazil. Blind spots in soil health research are found in Central and South America (excluding Brazil), Africa, Southeast Asia, and the Middle East. These regions harbor rich biodiversity but face the highest rates of deforestation, severe erosion, and significant threats from climate change. Our study highlights the urgent need for partnerships that empower underrepresented regions with scientific leadership and local tailored practices in order to restore soil health and address global crises within an achievable timeframe.